The Influence of Halal Labeling, Product Quality, and Price Perception on Purchasing Decisions of Halal Cosmetics in Pacitan Regency - Pika Hariyanto; Happy Agustiani (Golden Ratio of Data in Summary, 2026)
The development of the halal industry in Indonesia has encouraged the increasing public interest in the use of halal cosmetic products. This study aims to analyze the influence of halal labelization, product quality, and price perception on purchasing decisions of halal cosmetics in Pacitan. This study used a quantitative approach with a descriptive research type. The sampling technique used purposive sampling with a total of one hundred respondents who were users of halal cosmetics in Pacitan. Data collection was conducted through questionnaires using a Likert scale. Data analysis was carried out using SPSS through validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results showed that halal labelization had a positive and significant effect on purchasing decisions of halal cosmetics. Product quality also had a positive and significant effect on purchasing decisions and became the most dominant variable influencing consumer purchasing decisions. In addition, price perception had a positive and significant effect on purchasing decisions of halal cosmetics. Simultaneously, halal labelization, product quality, and price perception significantly influenced purchasing decisions of halal cosmetics in Pacitan. The results of this study indicate that consumers not only consider the halal aspect of products, but also product quality and price suitability in determining purchasing decisions of halal cosmetics.